Analisis Faktor –Faktor yang Mempengaruhi Minat Penggunaan Mobile Banking pada Mahasiswa Manajemen Universitas Andalas Kampus Payakumbuh - Maulidini Adha; Syuryatman Desri; Suci Humaira; Rian Septa Hadi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research uses descriptive research methods with a case study approach. The main aim of this research is to describe what factors influence interest in using mobile banking among management students at Anfalas University, Payakumbuh campus. The data collection process was carried out through literature study techniques and in-depth interviews. Based on the results of interviews that have been conducted, it was revealed that the interest and attraction of Management students at Andalas University, Payakumbuh Campus towards Mobile Banking revolves around the ease of carrying out transactions and checking account balances without the need to go to a Branch Office or ATM. Apart from that, interest in using Mobile Banking is also influenced by social factors. Mobile banking is a banking service that allows students to obtain information and carry out banking transactions via the Internet or cell phone with 24 hour access.